Non-viral transfection of bone marrow-derived mesenchymal stem cell with human interferon-gamma gene and in vitro efficiency against chronic myeloid leukaemia cells - Liew, Lee Chuen (2013)
Chronic myeloid leukemia (CML) is a hematopoietic stem cell disorder caused by the BCR/ABL gene rearrangement, known as the Philadelphia (Ph) chromosome. To date, the only curative therapy for CML is allogeneic stem cell transplantation. However, significant morbidity and mortality are associated with the procedure and the need for a matched donor makes this option not available to the majority of the patients. Currently, various studies have been carried out to develop an alternative approach for CML treatment, for example targeted gene delivery of therapeutic cytokines. In this study, the feasibility of using bone marrow-derived mesenchymal stem cell (BM-MSC) in delivering human interferon-gamma (hIFN-γ) gene for targeted CML therapy was explored. Mesenchymal stem cells (MSC) were successfully isolated from human bone marrow aspirates and their biological properties were similar to those of MSC reported. Expanded BM-MSC were transfected with plasmid containing hIFN-γ gene (pORF-hIFN-γ) via nucleofection. Gene transfer efficiency was determined based on intracellular hIFN-γ expression via flow cytometry and was found to be at 54.28±11.34%. The in vitro expression of hIFN-γ mRNA and protein in BM-MSC were also analysed at intervals of 24 h, up to 5 days post nucleofection, via real-time PCR and ELISA, respectively. Real-Time PCR data analysis showed significant up-regulation of hIFN-γ mRNA in nucleofected BM-MSC when compared to non-transfected BM-MSC (P=0.043). BM-MSC harbouring pORF-hIFN-γ could express hIFN-γ protein in vitro. This cytokine production was achieved as high as 3.47±1.03 ng/ml after 72 hours of nucleofection. The effect of hIFN-γ produced in nucleofected BM-MSC on the proliferation of CML cell line (K562) in vitro was also investigated. K562 growth was inhibited at 61.12±16.38% after seven days of co-culture with BM-MSC expressing hIFN-γ (P=0.006). In conclusion, findings in the current study indicated that hIFN-γ produced by genetically engineered BM-MSC successfully inhibited the proliferation of K562 cells in vitro. Thus, MSC as cellular vehicle in hIFN-γ gene delivery could be further explored as a promising treatment option for CML patients.